Audit committees in Singapore - Ho, Su Fern (2014)
The purposes of this project are to make a detailed study of the audit committees in Singapore with regard to their role and structure, to determine the degree of compliance with section 201B of the Companies Act (Cap. 50), to ascertain the need for audit committees in Singapore and to evaluate their effectiveness.